The Impact of Transformational Leadership on Employee Performance: Mediating Role of Meaningful Work - Icha Nursafitri Hafisrawati Suwandi; M. Musafir; Marten Puyo (Golden Ratio of Data in Summary, 2026)
Leadership plays a crucial role in shaping employees' perceptions of work and performance, particularly in public sector organizations. However, empirical findings on the relationship between transformational leadership and employee performance remain inconclusive, indicating the need to examine underlying psychological mechanisms. This study aims to analyze the effect of transformational leadership on employee performance, both directly and indirectly through meaningful work as a mediating variable. This study employs a quantitative explanatory approach using a survey method. Data were collected from employees of the Gorontalo Provincial Secretariat Office and analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The measurement model was evaluated through validity and reliability testing. In contrast, the structural model was assessed using path coefficients, coefficient of determination (R²), and significance testing to examine both direct and indirect effects. The results indicate that transformational leadership has a positive and significant direct effect on employee performance (β = 0.624; p < 0.001). In addition, transformational leadership positively and significantly influences meaningful work (β = 0.965; p < 0.001), and meaningful work has a positive and significant effect on employee performance (β = 0.359; p = 0.047). Meaningful work significantly mediates the relationship between transformational leadership and employee performance (β = 0.346; p = 0.046), indicating that leadership effectiveness is strengthened when employees perceive their work as meaningful. These findings demonstrate that transformational leadership enhances employee performance not only through direct influence but also by fostering meaningful work as a psychological mechanism. The study highlights the importance of integrating leadership practices with efforts to strengthen employees' sense of purpose and intrinsic motivation to achieve sustainable performance improvement in public sector organizations.